Imagens e promoção da compreensão no ensino da língua no 1º Ciclo do Ensino Básico (2017)
This paper while approaching the work of Jorge Bucay, illustrated by Gusti, The elephant in chains, discusses possible teaching practices of inferential reading comprehension in Primary School reflecting upon verbal and visual literacy issues. This approach aim to develop integrated skills (language and social) and to show that dialectical, substitutive and transmuting relations between text and image, when the text is carefully selected, are more productive in promoting reading skills than merely interpretative relations between text and image. Assuming that texts used in Elementary School are often bimodal texts (verbal and pictorial) it is urgent to develop reading strategies that go beyond the merely denotative function, promoting the aesthetic enjoyment, but also the ability to understand connotative meanings, inferences and trigger grammatical skills development tasks